Ihram when aligning the miqat with the plane"A comparative study" - Loay Hassan Jaber Al-Shami; dr. Abbas Ali Sultani; dr. Muhammad Hassan Haeri (Journal of College of Education, 2024)
The article deals with a topic that addresses the problem of the disagreement between the schools of jurisprudence regarding the issues that arise from entering ihram by aligning the miqat with an airplane. Which is considered one of the most important new and emerging issues in Hajj, as the research emphasized the clarification of some important introductions through which it is noted that most of those who fell into a state of confusion were as a result of not noticing these introductions. Then the research delved into a detailed explanation of the issue by presenting the opinions and sayings of the scholars of the schools of thought. Jurisprudence and its evidence with its jurisprudential analysis using the method of jurisprudential reasoning, and the research concluded with a statement of the correct opinion. This removes the state of confusion and illusion resulting from incorrect applications of the research topic.On the basis of this, the subject of the research was to compare the opinions of the two parties on the issues that introduced ihram, such as aligning the miqat with the plane, and to come up with the correct final result after presenting the evidence of the two parties, discussing it, and analyzing it jurisprudentially.The research contains three sections: the first section dealt with an explanation of some preliminary demands, the second section dealt with: the ruling on entering ihram from the miqat, and the last section dealt with the jurisprudential foundations of the issue of ihram from the line of the miqat on an airplane.Thus, our research has corrected the path followed and guided specialists to the paths of guidance, and from God Almighty we derive help and guidance.
Keywords: Ihram, alignment, miqat, comparative study